Implementation Of Integrated Quality Management of Education (MMTP) In Islamic Education Institutions - Yacub, Jamiluddin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this research is to find out how the Implementation of Integrated Quality Management of Education (MMTP) in Islamic educational institutions. The method used in this research is a literature study approach through literature sources and from various other literature sources. Then analyzed and presented the findings of the data objectively. The results showed that the Implementation of Integrated Quality Management of Education (MMTP) in Islamic educational institutions aims to improve the overall quality of education. Through a systematic approach that includes planning, implementation, supervision and evaluation, MMTP helps institutions achieve high educational standards. Collaboration between managers, educators, students and parents is the key to success, creating a conducive learning environment. The application of MMTP principles also focuses on developing teacher competencies and relevant curricula, as well as continuous improvement. Thus, MMTP not only improves academic aspects, but also shapes students' character and moral values, in line with the comprehensive goals of Islamic education.